Child with intranasal meningoencephalocele within the middle turbinate: case report - da Silva, Aldo Jose F.; Lima, Diego de Oliveira (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Cephalocele or encephalocele consists of the herniation of cranial contents through a bony defect in the skull. An occipital meningoencephalocele is the most common whereas an intranasal meningoencephalocele is a rare type of cephalocele. Here, we report a case of an intranasal meningoencephalocele within the middle turbinate. A 9-year-old male child was admitted to the emergency department due to epistaxis and difficulty breathing. Computed tomography (CT) and magentic resonance imaging (MRI) results revealed herniation of a voluminous, predominantly cystic lesion next to the cribriform plate, extending into the right middle conus. During endoscopic endonasal surgery, a bulging middle turbinate was visualized and the herniated sac was found to be inside the turbinate. The herniated sac, together with the middle turbinate, was resected. The patient presented good evolution, with no signs of cerebrospinal fluid fistula. Intranasal meningoencephalocele is rare. Usually, the herniation is between the middle turbinate and the nasal septum, unlike in this case, where it was within the middle turbinate itself. Clinical symptoms can vary and include nasal obstruction, anosmia, rhinorrhea, epistaxis and meningitis. Imaging studies (CT and MRI) help with differential diagnosis (polyps, nasal glioma, dermoid cyst, teratoma, mucocele) and surgical planning. Surgical treatment can be open or endoscopic, as in the case reported here. In children with nasal masses, especially when there are no signs of cerebrospinal fluid fistula, intranasal meningoencephalocele should be considered, thus avoiding puncture or biopsy.